Halichoerus grypus - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Halichoerus grypus (Fabricius, 1791). Skr. Nat. Selsk. Copenhagen, 1 (2):167. TYPE LOCALITY: Greenland (Denmark). DISTRIBUTION: Newfoundland area; Iceland; Britain; Norway; Kola Peninsula (U.S. S. R.). ISIS NUMBER: 5301413002003001001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Carnivora, pp. 244-289 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 286, DOI: 10.5281/zenodo.7352980